Cost-Effectiveness Analysis of No Adjuvant Therapy Versus Partial Breast Irradiation Alone Versus Combined Treatment for Treatment of Low-Risk DCIS: A Microsimulation. Issue 8 (August 2021) - Ward, Matthew C.; Vicini, Frank; Al-Hilli, Zahraa; Chadha, Manjeet; Abraham, Abel; Recht, Abram; Hayman, James; Thaker, Nikhil; Khan, Atif J.; Keisch, Martin; Shah, Chirag
Abstract : PURPOSE: Adjuvant therapy in patients with ductal carcinoma in situ who undergo partial mastectomy remains controversial, particularly for low-risk patients (60 years or older, estrogen-positive, tumor extent < 2.5 cm, grade 1 or 2, and margins ≥ 3 mm). We performed a cost-effectiveness analysis comparing three strategies: no adjuvant treatment after surgery, a five-fraction course of accelerated partial breast irradiation using intensity-modulated radiation therapy (accelerated partial breast irradiation [APBI]–alone), or APBI plus an aromatase inhibitor for 5 years. MATERIALS AND METHODS: Outcomes including local recurrence, distant metastases, and survival as well as toxicity data were modeled by a patient-level Markov microsimulation model, which were validated against trial data. Costs of treatment and possible adverse events were included from the societal perspective over a lifetime horizon, adjusted to 2019 US dollars and extracted from Medicare reimbursement data. Quality-adjusted life-years (QALYs) were calculated based on utilities extracted from the literature. RESULTS: No adjuvant therapy was the least costly approach ($5, 744), followed by APBI-alone ($11, 070); combined therapy was costliest ($16, 052). Adjuvant therapy resulted in slightly higher QALYs (no adjuvant, 11.320; APBI-alone, 11.343; and combination, 11.381). In the base case, no treatment was the cost-effective strategy, with an incremental cost-effectiveness ratio of $239, 109/QALY for APBI-alone and $171, 718/QALY for combined therapy. The incremental cost-effectiveness ratio for combined therapy compared with APBI-alone was $131, 949. Probabilistic sensitivity analyses found that no therapy was cost effective (defined as $100, 000/QALY of lower) in 63% of trials, APBI-alone in 19%, and the combination in 18%. CONCLUSION: No adjuvant therapy represents the most cost-effective approach for postmenopausal women 60 years or older who receive partial mastectomy for low-risk ductal carcinoma in situ.